Evolving role of positron emission tomography (PET) in urological malignancy. (25th May 2015) - Mafeld, Sebastian; Vasdev, Nikhil; Patel, Amit; Ali, Tamir; Lane, Timothy; Boustead, Gregory; Thorpe, Andrew C.; Adshead, James M.; Haslam, Philip
<x xml:space="preserve">Abstract</x> We present a review on the increasing indications for the use of positron emission tomography (PET) in uro‐oncology. In this review we describe the details of the different types of PET scans, indications for requesting PET scans in specific urological malignancy and the interpretation of the results.